2021
DOI: 10.3390/polym13071055
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties and Low-Velocity Impact Behavior of Polyamide 11/Basalt Fiber Fabric Laminates

Abstract: Environmentally friendly composite plates intended for load-bearing applications were prepared and systematically characterized in terms of mechanical performances and morphological features. Sample plates combining two extrusion grades of bio-polyamide 11, one of which is plasticized, and two basalt fiber fabrics (plain weave and twill architectures) were obtained by film stacking and hot pressing, and their mechanical properties were investigated by quasi-static flexural and low-velocity impact tests. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This damage degree is achieved at 20 J for the present work composite entailing a significant improvement in impact resistance. Furthermore, Vitiello et al [45] evaluated the impact resistance of PA11/basalt composites with a fiber volume fraction of 0.45 and a thickness of 3 mm. Their composites display peak forces and maximum displacements comparable with the ones obtained in this work but are characterized by a damage degree almost 30-60% lower.…”
Section: Low-velocity Impactsmentioning
confidence: 99%
“…This damage degree is achieved at 20 J for the present work composite entailing a significant improvement in impact resistance. Furthermore, Vitiello et al [45] evaluated the impact resistance of PA11/basalt composites with a fiber volume fraction of 0.45 and a thickness of 3 mm. Their composites display peak forces and maximum displacements comparable with the ones obtained in this work but are characterized by a damage degree almost 30-60% lower.…”
Section: Low-velocity Impactsmentioning
confidence: 99%
“…The [0/90] configuration featured intermediate quasi-static properties with a flexural stiffness closer to the [0/0] upper limit. The obtained results are promising, considering that Vitiello et al [43] reported a 15.7 GPa flexural stiffness and a 174 MPa flexural strength for a regular PA11 matrix reinforced with a basalt 2 × 2 twill, and Vitiello et al [44] acknowledged a bending stiffness of around 13 GPa and a strength of around 130 MPa for a PA11 reinforced with a plain-weave basalt fabric. The results compare favorably even with more traditional composite configurations, such as polypropylene (PP) glass-reinforced ones.…”
Section: Flexural Characterizationmentioning
confidence: 75%
“…[17][18][19][20][21][22][23] Basalt is a rock of volcanic origin that can be transformed into fibers with a melt spinning process similar to that used for the production of glass fibers. Over the last few years, the easy handling, reduced abrasiveness and low cost have fueled a growing and rapid interest in these fibers as valid alternatives to conventional ones, [24][25][26][27][28] and experimental indications are available on the preparation and characterization of many thermoplastic polymers, [29][30][31][32] including basalt fibres.…”
Section: Introductionmentioning
confidence: 99%